Robust sliding mode control of an electrorheological suspension system with parameter perturbations. (23rd February 2004) - Han, S.S.; Choi, S.B.; Park, J.S.; Kim, J.H.; Choi, H.J.
This paper presents a robust feedback control of an electrorheological (ER) vehicle suspension system with parameter uncertainties. There exist various types of uncertainties in practical vibration control of an ER suspension system, for example, the yield stress of ER fluid that is varied with the operation temperatures, and the sprung mass is to be changed by the number of riding persons and payload. Therefore, it is necessary to design a robust controller, which compensates parameter uncertainties for a vehicle featuring ER suspension system. After identifying the yield stress variation of the employed ER fluid with respect to temperatures, a quarter-vehicle ER suspension system with parameter uncertainties is constructed. A robust sliding mode controller, which has inherent robustness against system uncertainties, is then formulated by treating the sprung mass and the yield stress of the ER fluid as uncertain parameters. For the demonstration of robustness and performance of the proposed sliding mode controller, control responses such as vertical displacement and acceleration are presented in time and frequency domains.